Molecular Docking of Citrus amblycarpa Active Compounds against FTO, Leptin, and Resistin Protein - Roselina Panghiyangani; Juliyatin Putri Utami; Muhammad Akbar Baitullah; Novi Dwi Maulida (Molecular and Cellular Biomedical Sciences, 2023)
Background: Citrus amblycarpa has been known to have various pharmacological activities, such as antioxidants, anticancer, antitumor, hepatoprotective, anti-inflammatory, antidiabetic, antiviral, antibacterial, and antifungal. Hesperidin, naringin, quercetin, rutin, gamma (γ)-aminobutyric acid (GABA), neoeriocitrin, and poncirin from C. amblycarpa were the major constituents that potentially act on some obesity proteins, such as fat mass and obesity-associated (FTO) protein, leptin, and resistin, the emerging targets in the treatment of obesity. This study aimed to investigate the interaction between major active compounds of C. amblycarpa with FTO, leptin and resistin.Materials and methods: The ligands of the docking study were seven major chemical compounds found in peel of C. amblycarpa, i.e., hesperidin, naringin, quercetin, rutin, GABA, neoeriocitrin, and poncirin. FTO, leptin and resistin structure were taken from Protein Data Bank, while the C. amblycarpa compounds were prepared using Open Babel integrated into PyRx 8.0. Molecular docking simulation was performed using Autodock Vina integrated into PyRx 8.0. Virtual prediction and visualization of protein–ligand complexes were analyzed and visualized using Discovery Studio.Results: All major compounds of C. amblycarpa peel used in this study did not have hepatotoxicity and AMES toxicity. Hesperidin had the lowest binding affinity score when interacted with FTO, leptin and resistin compared to other compounds. Moreover, GABA had the highest binding affinity score compared to other compounds.Conclusion: Hesperidin may be a candidate obesity protein antagonist and may have potential as a treatment for obesity.Keywords: Citrus amblycarpa, molecular docking, FTO, leptin, obesity, resistin